Impact of cardiac resynchronization therapy optimization inside a heart failure programme: a real‐world experience. (24th June 2022) - Moulin, Thibaut; Hamon, David; Djouadi, Kamila; D'Humières, Thomas; Elbaz, Nathalie; Boukantar, Madjid; Zerbib, Céline; Rouffiac, Ségolène; Dhanjal, Tarvinder S.; Ernande, Laura; Derumeaux, Geneviève; Teiger, Emmanuel; et al.
Abstract: Aims: This study sought to describe and evaluate the impact of a routine in‐hospital cardiac resynchronization therapy (CRT) programme, including comprehensive heart failure (HF) evaluation and systematic echo‐guided CRT optimization. Methods and results: CRT implanted patients were referred for optimization programme at 3 to 12 months from implantation. The program included clinical and biological status, standardized screening for potential cause of CRT non‐response and systematic echo‐guided atrioventricular and interventricular delays (AVd and VVd) optimization. Initial CRT‐response and improvement at 6 months post‐optimization were assessed with a clinical composite score (CCS). Major HF events were tracked during 1 year after optimization. A total of 227 patients were referred for CRT optimization and enrolled (71 ± 11 years old, 77% male, LVEF 30.6 ± 7.9%), of whom 111 (48.9%) were classified as initial non‐responders. Left ventricular lead dislodgement was noted in 4 patients (1.8%), and loss or ≤90% biventricular capture in 22 (9.7%), mostly due to arrhythmias. Of the 196 patients (86%) who could undergo echo‐guided CRT optimization, 71 (36.2%) required VVd modification and 50/144 (34.7%) AVd modification. At 6 months post‐optimization, 34.3% of the initial non‐responders were improved according to the CCS, but neither AVd nor VVd echo‐guided modification was significantly associated with CCS‐improvement. After one‐year follow‐up, initial non‐responders maintained a higher rate of major HF events than initial responders, with no significant difference between AVd/VVd modified or not. Conclusions: Our study supports the necessity of a close, comprehensive and multidisciplinary follow‐up of CRT patients, without arguing for routine use of echo‐guided CRT optimization.